Valve‐sparing aortic root reconstruction in patient with prior renal transplantation. Issue 1 (6th November 2014) - Ueki, Chikara; Sakaguchi, Genichi; Akimoto, Takehide; Shintani, Tsunehiro
Key Clinical Message We describe a David operation in a 62‐year‐old renal transplant recipient with valsalva aneurysm and concomitant aortic insufficiency. The risk of postoperative infection seemed significant because he was receiving immunosuppressive therapy; thus, David operation was performed. He recovered uneventfully. David operation appears to be an attractive alternative in transplant recipients.